The Design and Development of Backend System for a Game Application - Louis Joshua Tandey (Bina Nusantara University, 2018)
This paper is discussed a technical report regarding the backend system and the web application to manage the game and the API that the game client of Dishcover Indonesia will frequently request to a web application is one of the many ways that can be used to manage content that is saved on the backend for a system. An API is also a method. The author, part of a team development for a game, will attempt to provide a solution so that to easily maintain the content of the game and a method for the client to access with them.